General View of Modern Education Problems in Indonesia: (Tinjauan Umum Problematika Pendidikan Modern di Indonesia) - Norhasan Norhasan (Sekolah Tinggi Ilmu Tarbiyah (STIT) Aqidah Usymuni, 2019)
The modern era has undergone many problems for the educationalinstitutions. The problems are not only about the concept, regulation andbudgeting but they are also regarding to the implementation of any kindsof education system in Indonesia. Some people say that the output of oureducation does not satisfy their demand of national education purpose.The morality and work ethic are still low. The corruption rate isincreasing and increasing. In addition, it is said that the employment inthis country is also adding. This condition makes us sad to face. Somesay, there’s something wrong in our education institution and it needsbetter improving and developing. This paper is pretended to analyse themodern education problems and the factors causing to make problems. Inthis paper, the writer would like to give the way out to overcome themodern education problems.